Cancer-specific PERK signaling drives invasion and metastasis through CREB3L1. Issue 1 (December 2017) - Feng, Yu-Xiong; Jin, Dexter; Sokol, Ethan; Reinhardt, Ferenc; Miller, Daniel; Gupta, Piyush
Abstract PERK signaling is required for cancer invasion and there is interest in targeting this pathway for therapy. Unfortunately, chemical inhibitors of PERK's kinase activity cause on-target side effects that have precluded their further development. One strategy for resolving this difficulty would be to target downstream components of the pathway that specifically mediate PERK's pro-invasive and metastatic functions. Here we identify the transcription factor CREB3L1 as an essential mediator of PERK's pro-metastatic functions in breast cancer. CREB3L1 acts downstream of PERK, specifically in the mesenchymal subtype of triple-negative tumors, and its inhibition by genetic or pharmacological methods suppresses cancer cell invasion and metastasis. In patients with this tumor subtype, CREB3L1 expression is predictive of distant metastasis. These findings establish CREB3L1 as a key downstream mediator of PERK-driven metastasis and a druggable target for breast cancer therapy. PERK stress signaling is an important driver of cancer invasion and metastasis, but chemical inhibitors of PERK cause side effects. Here, the authors find that CREB3L1 is required for PERK's pro-metastatic function in breast cancer, and its inhibition suppresses cancer invasion and metastasis.